The pyrrolidine ring and its relation with the psychoactivity of mitragynine - Mohd Ghazali, Masitah; Ridzwan, Irna Elina; Suhaimi, Maryam Saadah; Kasmuri, Abdul Razak; Hashim, Ridzwan; Aziz, Mohd Razif; Syd Mohmad Faudzi, Syed Mohd Syahmi (2015)
Mitragynine, the major alkaloid of Mitragyna speciosa has been widely studied for its anti-addictive properties. Similar to morphine, mitragynine mainly acts at mu-opioid receptor which is the main target to treat opioid dependency. Unfortunately, it is believed that the psychoactivity of mitragynine is limiting its use. Compared to morphine, mitragynine contains pyrrolidine ring in its chemical structure, which is suspected as the contributor to the unwanted psychoactive activities seen. Therefore, the aim of this study is to investigate the relationship between pyrrolidine ring and mitragynine’s psychoactive effects. This was done by synthesizing an analogue of mitragynine with epoxy ring to replace pyrrolidine. A tail-flick test (52°C) was conducted in vivo using ICR mice in order to establish the basal analgesic effect for mitragynine mediated by the mu-opioid receptor, with morphine as standard reference. 80 mg of mitragynine was found to be equipotent to 10 mg of morphine (n = 6, P < 0.001). The analogue of mitragynine (that has epoxy ring instead of pyrrolidine ring) was generated by total synthesis using 2-benzofuran-3-yl-ethylamine as the starting material involved three major reaction steps. Each intermediates and reaction products were purified using column chromatography. The analogue has been confirmed using 1H-NMR, 13-C NMR and Mass Spectra. This analogue was then evaluated using the tail-flick test to identify the activity of any mu-opioid receptor of the new analogue. The psychoactivity of this new analogue is currently under evaluation in vivo using an open-field test in ICR mice to observe any behavioural activity related to psychoactive effects. The intensity will be compared to mitragynine.